Comparison of intensity modulated radiotherapy plan optimisation methods for a 1.5 T MR‐Linac. Issue 1 (29th October 2018) - Chuter, Robert; van Herk, Marcel; Akhiat, Hafid; Voet, Peter; MacKay, Ranald; Choudhury, Ananya; McWilliam, Alan
Abstract: Purpose: For the 1.5 T Elekta MR‐Linac it is essential that the optimisation of a treatment plan accounts for the electron return effect on the planned dose distribution. The ability of two algorithms for the first stage fluence optimisation, pencil beam (PB) and Monte Carlo (MC), to produce acceptable plan quality was investigated. Optimisation time for each algorithm was also compared. Methods: Ten head and neck patients, ten lung patients and five prostate patients were selected from the clinical archive. These were retrospectively planned using a research version of Monaco with both the PB and MC algorithms for the fluence optimisation stage. After full optimisation DVH parameters, optimisation time and the number of Monitor Units (MU) as a measure of plan complexity were extracted. Results: There were no clinically significant differences between any of the DVH parameters studied or the total number of MUs between using PB or MC for stage 1 optimisation across the three patient groups. However, planning time increased by a factor of ten using MC algorithms for stage 1. Conclusion: The use of MC calculations compared to PB, for stage 1 fluence optimisation, results in increased planning time without clinical improvement in plan quality or reduction in complexity and is therefore not necessary.